Ochratoxin A Contamination of Food from Croatia - Peraica, Maja (MDPI, 2010)
Ochratoxin A (OTA) is a mycotoxin with nephrotoxic, genotoxic and carcinogenic properties produced by Penicillium and Aspergillus moulds under different climatic conditions. Humans and animals are exposed to this compound mainly via ingestion of contaminated food. In Croatia, research on mycotoxins focused on OTA when the mycotoxin theory of endemic nephropathy (EN) was postulated. Ochratoxin A was more frequent and at higher concentration in foods from EN than those from the control regions. Subsequently, OTA concentrations were determined in some commodities intended for human consumption such as maize, wheat, beans and wine. Samples from all parts of Croatia were analyzed and OTA was found in all types of commodities. It was frequently found together with other mycotoxins (fumonisin B(1), fumonisin B(2) and zearalenone). In general, OTA concentration in foods from Croatia is low, but the frequency of positive samples shows considerable variations from year to year depending also on sampling location. Although low levels of OTA were found in a large proportion of analyzed food samples, its persistent co-occurrence with other significant mycotoxins should raise serious public health concerns as there interactions may be synergistic or additive in causing toxicity in humans and animals. There is need to establish control measures through which such contaminations in foods can be managed.